DETERMINACIÓN DE Salmonella spp EN CENTROS DE BENEFICIO CLANDESTINO DE POLLOS DE ENGORDE EN LIMA, PERÚ - Zambrano F., Hatzumi (2013)
The aim of this study was to determine the presence of Salmonella spp in broilers from 17 illegal abattoirs in Lima, Peru. Samples were collected from the body surface of carcasses (using the rinsing method) and cloacal swabs in 170 broilers. The isolation and identification of Salmonella spp was done through conventional laboratory methods. Results showed 23.5% of body surface samples and 32.4% of the cloacal swabs were positive to Salmonella spp, without differences between abattoirs where evisceration was or was not carried out. The degree of concordance of the results for both sampling methods was not significant (k = 0.074, k = 0.146), indicating the both types of samples have to be taken to determine possible contaminations of the carcasses by Salmonella spp.